2020
DOI: 10.1080/16549716.2020.1788261
|View full text |Cite
|
Sign up to set email alerts
|

Quality of family planning services for women of reproductive age in Lao PDR

Abstract: Background: In Lao PDR, 15% of the married women want to postpone or prevent having a child, yet most are not using contraceptives to achieve this. Literature shows that usage of contraceptives is strongly dependent on the quality of family planning services. However, little is known about the quality of family planning services in Lao PDR. Objective: To assess the quality of family planning services provided in public health facilities in Lao PDR. Methods: Using a cross-sectional study design, public health f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…This aligns with similar research from the Philippines noting that even amid social disapproval of premarital sex, many young people engage in sexual relations before cohabitation or marriage [41,42]. Others have noted that while premarital sex is stigmatised and not socially accepted in Lao culture [12,17,34], in certain areas (i.e., rural, and rural-off-road) and ethnic minority communities, traditional values, beliefs, and practices are more permissive regarding adolescent premarital sexual relations [10,18,43].…”
Section: Attitudes and Norms Regarding Sex And Pregnancy Outside Of U...supporting
confidence: 83%
See 1 more Smart Citation
“…This aligns with similar research from the Philippines noting that even amid social disapproval of premarital sex, many young people engage in sexual relations before cohabitation or marriage [41,42]. Others have noted that while premarital sex is stigmatised and not socially accepted in Lao culture [12,17,34], in certain areas (i.e., rural, and rural-off-road) and ethnic minority communities, traditional values, beliefs, and practices are more permissive regarding adolescent premarital sexual relations [10,18,43].…”
Section: Attitudes and Norms Regarding Sex And Pregnancy Outside Of U...supporting
confidence: 83%
“…Though there are no laws that explicitly prohibit young people from accessing SRH services [32], existing policies (e.g., 2019 National Sexual and Reproductive, Maternal, Newborn, Child and Adolescent Health Policy) lack specific guidance on parental consent requirements for minors to access contraceptives [33]. In the absence of laws or specific guidance, parental consent requirements are subject to healthcare providers' discretion [33], and recent research suggests that healthcare providers could be limiting adolescents' access to family planning services [34], especially since sex outside of marriage is socially unacceptable in Lao culture [12].…”
Section: Barriers To Srh Information and Services Including Contracep...mentioning
confidence: 99%
“…Kader KB dalam pelayanan kontrasepsi memiliki peran vital dalam pemberian komunikasi, informasi dan edukasi (KIE) secara rinci agar Pasangan Usia Subur (PUS) bersedia menggunakan kontrasepsi metode kontrasepsi jangka panjang dalam hal ini adalah kontrasepsi implan (Rusmin et al, 2019;Sulastri et al, 2019) (Danna et al, 2021;Rocca et al, 2021). Akseptor juga merasa penting mendapatkan informasi tentang kontrasepsi yang diberikan dan penggunaannya diberikan, walaupun di lapangan tidak selalu dilakukan dengan ideal seperti yang diharapkan oleh akseptor (Thongmixay et al, 2020). Kehandalan, perilaku, komunikasi, dan pendekatan yang tepat dari provider mempengaruhi nilai pelayanan dan kepuasan pengguna layanan kesehatan (Manzoor et al, 2019;Park et al, 2021;Reyes-Martí et al, 2021).…”
Section: Pembahasanunclassified
“…Other studies have identified a range of factors that can promote or inhibit QC for family planning. 6,7,[10][11][12][13][14][15][16][17] However, these prior studies sometimes focused only on clients' or providers' perspectives or used survey methods that assume the factors are known well enough to be limited to closed-ended survey questions. Most of these other studies were also conducted in other countries.…”
Section: Highlightsmentioning
confidence: 99%